Analisis Dampak Hilirisasi Industri Kakao di Indonesia: Kata Kunci: Kakao, Rantai Nilai, Hilirisasi Industri, and Value Added - Sebastian Hadinata; Maria Merry Marianti (Jurnal Akuntansi, 2020)
Cocoa is one of Indonesia’s plantation commodity that is important for the national economy. Cocoa plays a role in encouraging regional development and agro-industry. The purpose of this study was to find out the cocoa value chain in Indonesia and find out the impact of the downstream cocoa processing industry in Indonesia. The method used is literature study. The results of the analysis show that the downstreaming of the cocoa processing industry has a positive impact on Indonesia, the benefits of which are getting value added of raw material products, strengthening industrial structures, providing employment, attracting investors, and providing business opportunities in Indonesia.